2015
DOI: 10.1371/journal.pone.0122674
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Profiling of Atrial Fibrillation in Canines: MiR-206 Modulates Intrinsic Cardiac Autonomic Nerve Remodeling by Regulating SOD1

Abstract: BackgroundA critical mechanism in atrial fibrillation (AF) is cardiac autonomic nerve remodeling (ANR). MicroRNAs (miRNAs) are small non-coding RNAs that regulate gene expression at the post-transcriptional level. Numerous miRNAs are involved in diseases of the nervous and cardiovascular systems.ObjectiveWe aimed to assess the underlying role of miRNAs in regulating cardiac ANR in AF by right atrial tachypacing (A-TP) in canines.Methods and ResultsFollowing 4-week A-TP, the superior left ganglionated plexuses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 44 publications
2
43
0
1
Order By: Relevance
“…Gene therapy of a canine model with a lentivirus containing miR-206 resulted in truncation of the atrial APD beyond what was seen with atrial tachypacing alone. Accordingly, treatment with a lentivirus containing the antagonist anti-miR-206 resulted in AERP prolongation and reduced inducibility of AF (47). …”
Section: Targets For Gene Therapymentioning
confidence: 99%
“…Gene therapy of a canine model with a lentivirus containing miR-206 resulted in truncation of the atrial APD beyond what was seen with atrial tachypacing alone. Accordingly, treatment with a lentivirus containing the antagonist anti-miR-206 resulted in AERP prolongation and reduced inducibility of AF (47). …”
Section: Targets For Gene Therapymentioning
confidence: 99%
“…According to ZHANG et al (2015), microcfa-miR 206 is overexpressed 9.5 times more in dogs with AF when compared to dogs without arrhythmia. Expression of 16 other microRNAs is also dysregulated in dogs with AF.…”
Section: Arrhythmiasmentioning
confidence: 99%
“…MicroRNAs are potentially involved in a wide range of biological and pathological events. They are composed of approximately 19 to 25 nucleotides (ZHANG et al, 2015), transcribed from intranuclear DNA and transported to the cytoplasm, where a pre-microRNA is cleaved into mature microRNAs ( Figure 1) (CREEMERS et al, 2012). Increasingly, new evidence points to the role of microRNAs in the pathogenesis of several diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The authors found that KCNH2 transfer prolonged atrial action potential duration and prevented AF [9]. Similarly, Zhang's group found that miR-206 modulated intrinsic cardiac autonomic nerve remodeling in AF via right atrial tachypacing via the regulation of superoxide dismutase 1 (SOD1) in vivo, and this may be a potential therapeutic target for AF because it shortens the atrial effective refractory period [10]. Furthermore, many loci or target genes associated with ion channels, autonomic innervation, gap junctions, and substrate modifiers have been identified in preclinical studies to attenuate fibrosis, autonomic nerve sprouting, and AF duration [11][12][13].…”
Section: Introductionmentioning
confidence: 97%
“…That study underscores the fact that the pathogenesis of AF and its underlying molecular mechanisms are not completely understood. Recently, a series of preclinical studies suggested that genebased approaches could be used for the diagnosis and treatment of AF [9,10]. Most studies have had encouraging results that indicate the potential of gene-based therapies to combat AF.…”
Section: Introductionmentioning
confidence: 99%